2021
DOI: 10.3390/drones5030073
|View full text |Cite
|
Sign up to set email alerts
|

UASea: A Data Acquisition Toolbox for Improving Marine Habitat Mapping

Abstract: Unmanned aerial systems (UAS) are widely used in the acquisition of high-resolution information in the marine environment. Although the potential applications of UAS in marine habitat mapping are constantly increasing, many limitations need to be overcome—most of which are related to the prevalent environmental conditions—to reach efficient UAS surveys. The knowledge of the UAS limitations in marine data acquisition and the examination of the optimal flight conditions led to the development of the UASea toolbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Environmental conditions for detecting forage fish were evaluated through infield experiments using forage fish-like fishing lures and considering the influence of sun altitude, turbidity (secchi depth as a proxy), cloud cover, wind speed, and wave height. Generally, our findings showed that calm conditions with clear skies, moderate sun angles, and low turbidity to be optimal, similar to others working with different taxa, including eelgrass, sharks, and marine mammals [4,5,[21][22][23][28][29][30][31][32][33]. Defining these optimal conditions will help make RPAS surveys the basis of a practical, efficient, non-destructive, fishery independent technique for quantifying forage fish distribution and abundance [5].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Environmental conditions for detecting forage fish were evaluated through infield experiments using forage fish-like fishing lures and considering the influence of sun altitude, turbidity (secchi depth as a proxy), cloud cover, wind speed, and wave height. Generally, our findings showed that calm conditions with clear skies, moderate sun angles, and low turbidity to be optimal, similar to others working with different taxa, including eelgrass, sharks, and marine mammals [4,5,[21][22][23][28][29][30][31][32][33]. Defining these optimal conditions will help make RPAS surveys the basis of a practical, efficient, non-destructive, fishery independent technique for quantifying forage fish distribution and abundance [5].…”
Section: Introductionsupporting
confidence: 79%
“…The optimal range for sun altitudes between 20 • and 40 • balances the need for adequate solar irradiance to illuminate forage fish targets and avoid sun glint on the surface. Solar altitude is important, as a minimum amount of solar irradiance is required to adequately illuminate targets for visual identification [22,31,43] associated with the light attenuation properties of the water constituents, the characteristics of the target (e.g., color, size, depth in the water column), and the contrast between the target and the background [33]. Higher solar altitudes will deliver more solar irradiance.…”
Section: Environmental Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark Set-was to understand how differences in exposure and contrast affect the reliability of the automated pixel selection and object detection models. Indeed, one of the biggest problems with nadir images collected over the ocean is the glare from sunlight backscatter, resulting in "specs" of high reflectance that can be misidentified as white floating objects [95]. The use of these contrasting exposure settings were expected to have a major influence on colorand contrast-based analysis and identification of floating items due to the homogenization of the background (i.e., seawater) in underexposed images [36,78].…”
Section: Discussionmentioning
confidence: 99%